Evolução clínica e nutricional de um adolescente acompanhado em um centro de terapia intensiva de um hospital de ensino: Relato de caso - Silva, Alex Richard Costa; Orlandi, Daniele de Paula; Guandalini, Valdete Regina [UNESP] (My University, 2017)
Objective: Describe the clinical and nutritional evolution of an adolescent admitted to the Intensive Care Unit of a teaching hospital. Case Description: 18 years old adolescent, male, underwent hepatic transplantation in childhood due to chronic cholestasis of genetic etiology. He was hospitalized in the ward with convulsive seizures, upper airway inflammation, acute kidney injury (stage 3), with hypothetical diagnostic of H1N1 infection, nephrotoxicity by Tracolimus and glomerulopathy. He presented important tachydyspnea, evolving into acute respiratory failure, which is why he was brought to the Intensive Care Unit and submitted to orotracheal intubation. Comments: Chronic cholestasis and late hepatic post-transplant with the use of immunosuppressive drugs are related to the presence of protein-caloric malnutrition, low weight and height for the age in patients who do not undergo appropriate nutritional monitoring in long term and also to renal alteration, situations presented in this case. Enteral nutritional therapy was initially adopted for the patient while in the Intensive Care Unit. After extubation, he was weaned off it by introducing oral diet gradually. Conclusion: Despite the limitations in nutritional evaluation, due to the patient's clinical history, the planned nutritional therapy turned out satisfactorily and positively, with rapid adaptation to nutritional needs, which contributed to the improvement of biochemical parameters, decrease of the effects of protein-calorie malnutrition and clinical condition.
Clinical and nutritional evolution of an adolescent accompanied in an intensive care unit of a teaching hospital: Case report
Keywords: Adolescent; Critical care; Nutritional status; Protein-energy malnutrition